Validity, reliability, and feasibility of the digital motor performance test (DigiMot) - Klein, Thorsten; Pauli, Max; Greiner, Joann; Hanssen-Doose, Anke (Frontiers in Sports and Active Living, 2025)
IntroductionAssessing and monitoring physical fitness in children and adolescents requires valid, reliable, and feasible tests. The digital motor performance test (DigiMot) was developed for remote assessment via videoconference. This study evaluated its validity, reliability, and feasibility in children and adolescents.MethodsA total of 1,751 participants aged 5–17 years took part in this study. They completed four fitness tasks assessing coordination (Jumping Sideways), muscular endurance (Push-ups and Sit-ups), and flexibility (Stand-and-Reach). Validity was assessed by comparing remote and face-to-face performances (N = 60). Test–retest reliability was evaluated across two remote sessions (N = 96), and interrater reliability was analyzed using video-recorded sessions (N = 381). Feasibility was examined based on all available remote assessments (N = 1,751).ResultsConcurrent validity was good for Jumping Sideways (ICC = .844), Push-ups (ICC = .718), and Sit-ups (ICC = .831), with almost perfect agreement for Stand-and-Reach (κ = .850). Test–retest reliability ranged from good (Push-ups, ICC = .781) to excellent (Sit-ups, ICC = .940; Jumping Sideways, ICC = .913), with almost perfect agreement for Stand-and-Reach (κ = .845). Interrater reliability was excellent for Jumping Sideways (ICC = .972) and Push-ups (ICC = .967), good for Sit-ups (ICC = .873), and substantial to almost perfect for Stand-and-Reach (κ = .805). Completion rates exceeded 98%, with minimal technical issues.DiscussionThe DigiMot test demonstrates good to excellent validity, reliability, and feasibility, while addressing a relevant gap in remote physical fitness testing for children and adolescents.